Global Innovation of Teaching and Learning in Higher Education
XVI, 369 p. 5 illus. in color.
Keywords: This book examines current trends in higher education and the Scholarship of Teaching and Learning. It introduces readers to pedagogical strategies that instructors worldwide are using to overcome some of the challenges they face in higher education. To maximize their students’ learning, this work argues that institutions are compelled to innovate their policies and instructors must be collaborative and creative in their practices in response to students’ growing demands, needs, challenges to their learning, and the shifting terrain of a rapidly globalizing world. The text explores the idiosyncrasies and challenges that drive innovation across particular cultures, disciplines and institutions. It suggests that the responses to these drivers offer some universal and compatible lessons that not only optimize teaching and learning, but also transgress institutional, cultural, and disciplinary boundaries in higher education. The contributors to this collection work in the United States, the United Kingdom, Africa, Asia, Australia, Scandinavia and the Middle East. They represent a broad range of disciplines, fields and institutional types. They teach in varied contexts, durations, delivery modes, and formats, including online, study abroad, blended, accelerated, condensed, intensive and mortar-and-brick settings. Their higher education students are equally as diverse, in age, cultural backgrounds and needs, but willingly lend their voices and experiences to their instructors’ study of teaching and learning in their particular contexts. This book harnesses the rich diversities and range our contributors represent and shares the results of their expertise, research, and assessments of some of the most creative and effective ways to improve student learning in the face of stagnant practices, limited resources, and other deficiencies that instructors and students face inhigher education.